Is the tropical cyclone surge in Shanghai more sensitive to landfall location or intensity change? - Wang,S; Toumi,R; Ye,Q; Ke,Q; Bricker,J; Tian,Z; Sun,L (Atmospheric Science Letters, 2021)
It has been shown that the proportion of intense tropical cyclones (TCs) has been increasing together with a poleward migration of TC track. However, their relative importance to TC surge at landfall remains unknown. Here we examine the sensitivity of TC surge in Shanghai to landfall location and intensity with a new dynamical modelling framework. We find a surge sensitivity of 0.8 m (°N)−1 to landfall location, and 0.1 m (m s−1)−1 to wind speed in Shanghai during landfall. The landfall location and intensity are comparably important to surge variation. However, based on a plausible range of reported trends of TC poleward migration and intensity, the potential surge hazard due to poleward migration is estimated to be about three times larger than that by intensity change. The long-term surge risk in Shanghai is therefore substantially more sensitive to changes of TC track and landfall location than intensity. This may also be true elsewhere and in the future.